Hibridne strukturirane površine za izboljšan prenos toplote pri mehurčkastem vrenju - Može, Matic (visokošolska dela, 2021)
This work deals with nucleate boiling heat transfer and its enhancement through modification of the boiling surface and the interaction of the latter with the working fluid. To this effect, we present the development of hybrid structured surfaces, which promote nucleate boiling. Surfaces of aluminum, copper and titanium samples are functionalized using chemical or laser surface texturing and subsequent hydrophobization through application of a fluorinated silane. Analysis of reference critical heat flux values from literature shows that considerable scatter results from different methodologies of processing measured values. This was used to develop a new experimental setup for boiling performance evaluation with reduced measurement uncertainty. Boiling heat transfer was evaluated on developed surfaces using saturated pure water at atmospheric pressure. Developed surfaces exhibited critical heat flux values of up to 1943 kW m-2 (> 100 % enhancement over the reference surface) and heat transfer coefficients of up to 304,7 kW m-2 K -1 (> 500 % enhancement). We have shown that repeated onset of critical heat flux or long-term boiling on the surface changes morphological and chemical properties of the boiling surface, which affects boiling heat transfer. Boiling of self-rewetting fluids on developed hybrid structured surfaces resulted in deterioration of heat transfer intensity compared to boiling of pure water on the same surfaces, although heat transfer is still enhanced compared to boiling of these fluids on untreated surfaces. The results of the doctoral thesis demonstrate that properly degassed surfaces with low surface energy and nucleate-boiling-promoting microstructure provide substantial enhancements of nucleate boiling heat transfer parameters, which challenges the currently established sentiment that such (macroscopically superhydrophobic) surfaces are unsuitable for boiling heat transfer enhancement.
Keywords: Disertacije; dissertations; enhanced heat transfer; hibridne površine; hybrid surfaces; izboljšan prenos toplote; mehurčkasto vrenje; nucleate boiling; samoomočljivi fluidi; self-rewetting fluids; staranje površin; structured surfaces; strukturiranje površin; surface aging; Vrenje